Integrating AI in Military Decision-Making: A Review of Opportunities, Risks, and Governance - M. Thoriq Fadlullah; Agung Risdhianto; Heru Dewanto (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Integrating Artificial Intelligence (AI) into military operations creates a paradigm shift, introducing a profound tension between operational opportunities and severe risks to strategic stability. This paper conducts a systematic literature review to investigate this challenge, focusing on the transformation of Military Decision-Making. The analysis confirms that while AI offers significant capabilities in intelligence and logistics, it also introduces a triad of technical, strategic, and human-centric risks. These risks fuel a global arms race and create a crisis of accountability, particularly with the development of Autonomous Weapons. The central problem identified is a critical